Enhancement of transverse Kerr effect in a BiYIG based magneto optical device with metal nanopyramid arrays - Saeed Afrouzi; Vahid Fallahi; Reza Aghbolaghi; Hamze Ali Navid (Scientific Reports)
Abstract The magneto-optical device based on a periodic array of metal nanopyramids embedded in a film of Bi:YIG coated on the surface of a silver substrate, is optimized utilizing a computational simulation technique (CST Microwave Studio). Under coupling conditions through the two-dimensional grating, the TM-guided modes with narrow resonance are excited in the Bi:YIG film by the incident light, increasing hence the light-matter interaction. Such coupling results as the dips in the reflectance spectrum. The transverse magneto-optical Kerr effect (TMOKE) for a similar structure with a periodic array of rectangular nano-silver is around 4%, hence an enhancement with one order of magnitude was achieved through the proposed device. The surface plasmon polariton modes with the asymmetric narrowband spectral feature are presented in the diffraction of light by a grating in the near-wavelength regime for the TMOKE case, particularly the high reflectivity ( $$\sim 47%$$ ) and the high-quality factor resonances ( $$Q\sim 332$$ ). Hence, it would be a promising device for magnetic field sensing and even biosensing applications.